Analisys on the Implemetation of Integrated Social Service Model - Kissumi Diyanayati; Etty Padmiati (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2016)
The current social services as present are still sectoral, fragmented, limited outreach, respond only actual problem, output based on budget absorbtion, they have not yet reached outcome and impact. Law No 11, 2009 and Government Regulation No 39, 2012 state that social service should be acted orientically, integratedly, and continously by government and community. Social Ministry Decree No 50/HUK/2013 on, integrated social service and movement toward regency/municipality welfare, answers the need of integrity and community participation. An implementation of integrated social service in Payakumbuh Municipality is a program use action research approach that took three years (2013-2015)of implementation. The first year, was to shape Anak Nagari social service unit (UPT-KAN). The second year was focused on the implementation of social service as community claims began. Guidance and advocation in the third year succesfully set social welfare institution (LKS), named Mitra Kenanga, functioned as an institution that diburse community fund as UPT-KAN operationalitation, targeted data base making, and socialization on the institution existence. Fun resources of UPT-KAN hailed from social and menpower and health agency, BAZ, Mitra Kenanga, and CSR. The existence of UPTKANin its application has proved poor community and people with social welfare problem easily to get base social service especially those have been untouched by regular social service program.